AB0041 CD8+ T CELLS HAVE AN ELEVATED PROLIFERATIVE CAPACITY IN GIANT CELL ARTERITIS. (2nd June 2020) - Reitsema, R.; Hid Cadena, R.; Abdulahad, W.; Boots, A.; Heeringa, P.; Brouwer, E.
Abstract : Background: Giant cell arteritis (GCA) is the most frequent form of systemic vasculitis affecting the large- and medium-sized vessels. The involvement of innate immune cells and CD4+ T cells in the pathogenesis of GCA has been extensively studied. Interestingly, recent findings suggest a role for CD8+ T cells in disease development (1). However, CD8+ subsets and their functional capacities have not yet been studied in detail. Objectives: This study aims to characterize the phenotype and proliferative capacity of CD8+ T cells in newly diagnosed GCA patients and GCA patients in remission compared to healthy age- and sex- matched controls. Methods: To determine the phenotype of CD8+ T cells in GCA, newly diagnosed, untreated GCA patients (baseline, n=14), GCA patients in stable glucocorticoid-free remission (GC-FR, n=10) and age- and sex-matched healthy controls (HCs, n=18) were enrolled. Peripheral blood mononuclear cells (PBMCs) were stained with fluorochrome-conjugated antibodies directed against CD3, CD4, CD8, CCR7, CD45RO, Ki-67, CD69 and CD25 and analyzed by flow cytometry. The following differentiation subsets were defined: CD8+ T naive (CD45RO-CCR7+), central memory (TCM, CD45RO+CCR7+), effector memory (TEM, CD45RO+CCR7-) and effector memory re-expressing CD45RA (TEMRA, CD45RO-CCR7-) cells. Secondly, the proliferative capacity of CD8+ T cells was determined in isolated CD3+ T cells of 10 GCA baseline, 10 GCA GC-FR patients and 19 HCs after 5 days of stimulation with plate-bound anti-CD3 or anti-CD3 plus soluble anti-CD28 using a dye-based proliferation assay. Results: A reduced frequency of CD8+ TEM cells was found in GCA baseline patients compared to HCs (p=0.025). Furthermore, a higher frequency of Ki-67+ cells was detected among CD8+ TEM cells in GCA baseline patients than in HCs (p=0.0007), suggesting a higher proliferative activity in vivo. In addition, in vitro stimulation with anti-CD3 and anti-CD3+anti-CD28 led to higher percentages of divided CD8+ T cells in GCA baseline and GC-FR patients than in HCs (p<0.05). Moreover, the frequencies of CD8+ TEMRA cells and the percentage of divided CD8+ T cells upon CD3 stimulation strongly correlated in GCA baseline patients (R=0.79, p=0.009) and GCA GC-FR patients (R=0.67, p=0.039) but not in HCs (R=0.31, p=0.25). Conclusion: GCA baseline patients demonstrate a higher frequency of proliferating circulating CD8+ TEM cells, defined by Ki-67 expression, than HCs. In addition, functional data on induced proliferative capacity suggest that CD8+ T cells from GCA baseline patients are more rapidly activated by crosslinking CD3 and CD3+CD28, suggesting either reduced regulation in these patients or more intrinsic threshold changes. Furthermore, the induced proliferative capacity is also elevated in patients in stable glucocorticoid-free remission. Whether the increased proliferative capacity of total CD8+ T cells in GCA patients is causally linked to the increased frequencies of CD8+ TEMRA cells in these patients requires further investigation. References: [1]Samson M, Ly KH, Tournier B, Janikashvili N, Trad M, Ciudad M, et al. Involvement and prognosis value of CD8+ T cells in giant cell arteritis. J Autoimmun. 2016;72:73–83. Disclosure of Interests: Rosanne Reitsema: None declared, Rebeca Hid Cadena: None declared, Wayel Abdulahad: None declared, Annemieke Boots Consultant of: Grünenthal Gmbh until 2017, Peter Heeringa: None declared, Elisabeth Brouwer Consultant of: Roche (consultancy fee 2017 and 2018 paid to the UMCG), Speakers bureau: Roche (2017 and 2018 paid to the UMCG)